Apolipoprotein C-II: New findings related to genetics, biochemistry, and role in triglyceride metabolism. (December 2017) - Wolska, Anna; Dunbar, Richard L.; Freeman, Lita A.; Ueda, Masako; Amar, Marcelo J.; Sviridov, Denis O.; Remaley, Alan T.
Abstract: Apolipoprotein C-II (apoC-II) is a small exchangeable apolipoprotein found on triglyceride-rich lipoproteins (TRL), such as chylomicrons (CM) and very low-density lipoproteins (VLDL), and on high-density lipoproteins (HDL), particularly during fasting. ApoC-II plays a critical role in TRL metabolism by acting as a cofactor of lipoprotein lipase (LPL), the main enzyme that hydrolyses plasma triglycerides (TG) on TRL. Here, we present an overview of the role of apoC-II in TG metabolism, emphasizing recent novel findings regarding its transcriptional regulation and biochemistry. We also review the 24 genetic mutations in the APOC2 gene reported to date that cause hypertriglyceridemia (HTG). Finally, we describe the clinical presentation of apoC-II deficiency and assess the current therapeutic approaches, as well as potential novel emerging therapies. Highlights: ApoC-II is a cofactor for LPL and thus promotes hydrolysis of TG on TRL. It is part of the APOE/C1/C4/C2 gene cluster and undergoes complex regulation. ApoC-II prevents displacement of LPL from TRL during lipolysis. We summarize 24 novel mutations reported to cause apoC-II deficiency. Low-fat diet is the primary treatment but new therapies are under development.